2017
DOI: 10.1124/dmd.116.074732
|View full text |Cite
|
Sign up to set email alerts
|

Global Proteomic Analysis of Human Liver Microsomes: Rapid Characterization and Quantification of Hepatic Drug-Metabolizing Enzymes

Abstract: Number of tables: 2 Number of references: 54Number of words in the abstract: 246 Number of words in the introduction: 722Number of words in the discussion: 1450 Abbreviations ADME, absorption, distribution, metabolism and excretion; BSA, bovine serum albumin; DDI, drugdrug interaction; DME, drug-metabolizing enzyme; GO, Gene Ontology project; HLM, human liver microsomes; HPLC, high performance liquid chromatography; IMS, ion-mobility spectrometry; IVIVE, in vitro-in vivo extrapolation; LC-MS, liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 55 publications
3
65
0
Order By: Relevance
“…The limit of quantification was estimated as previously described (Achour et al . ) at 0.06 fmol of peptide on column (translating to protein abundance of 0.1 fmol/μg protein).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The limit of quantification was estimated as previously described (Achour et al . ) at 0.06 fmol of peptide on column (translating to protein abundance of 0.1 fmol/μg protein).…”
Section: Resultsmentioning
confidence: 99%
“…; Achour et al . ). Details of data analysis and quantification approaches are provided in Appendix S1.…”
Section: Methodsmentioning
confidence: 97%
“…A recent proteomics study has shown that CES1 is the most abundant drug‐metabolizing enzyme in human liver microsomes . As the predominant hepatic hydrolase, CES1 plays a critical role in the activation/deactivation of various medications.…”
Section: Discussionmentioning
confidence: 99%
“…20 Peptide separation is achieved on nano-LC, micro-LC, or conventional-LC systems, which can be further improved using ion mobility separation prior to MS analysis. 21,22 Analysis of precursor and product ions (mass filtering) can be achieved in space or in time depending on the mass analyzer. Selection of proteotypic peptides utilizes multiple in silico or experimental approaches and considers recommended criteria to ensure peptides are representative of target proteins ( Table 1).…”
Section: Basic Proteomics Workflowmentioning
confidence: 99%
“…For example, Na + /K + ATPase and calnexin have previously been used as markers for basolateral plasma membrane and reticular microsomal membrane, respectively. 22,31,37 STATE of the ART Membrane enrichment is carried out using various centrifugation or membrane extraction methods, often as commercial kits. A substantial amount of published transporter data are generated using these kits; however, no systematic assessment of the quality of kit-enriched fractions has been reported.…”
Section: Sample Quality and Characteristicsmentioning
confidence: 99%